A four‐step filtering strategy based on ultra‐high‐performance liquid chromatography coupled to quadrupole‐time‐of‐flight tandem mass spectrometry for comprehensive profiling the major chemical constituents of Akebiae Fructus. (8th August 2019) - Ma, Baolian; Yang, Shilin; Li, Junmao; Ouyang, Hui; He, Mingzhen; Feng, Yulin; Tan, Ting
Abstract : Rationale: Akebiae Fructus (AF) is a traditional Chinese medicine (TCM) with antiphlogistic, analgesic, antineoplastic, diuretic, antirheumatic, antidepressant and antiobesity activities. Identification of chemical constituents from AF is helpful to discover the potential active ingredients and to control its quality. Methods: The four‐step filtering strategy was as follows: (1) To extract the accurate mass by the different adduct ions. (2) To screen different types of the compounds using diagnostic ions. (3) By characteristic ion filtering, to confirm the substituted position and the sugar chain numbers. (4) Based on the neutral loss (NL), to identify the type of monosaccharide and the compositions of sugar chains of triterpenoid saponins and the structure of CGAs. Results: A total of 94 compounds (85 triterpenoid saponins, 9 chlorogenic acids) were unambiguously or reasonably identified. Fifty constituents were discovered for the first time from AF. Nine types of triterpenoid saponins, including akebonoic acid (type I), norhederagenin (type II), oleanolic acid (type III), 2α, 3β‐dihydroxy‐23‐oxo‐30‐norolean‐12, 20(21)‐dien‐28‐oic acid (type IV), gypsogenin (type V), norarjunolic acid (type VI), hederagenin (type VII), 2α, 3β‐dihydroxy‐23‐oxo‐olean‐12‐en‐28‐oic acid (type VIII), arjunolic acid (type IX), and two types of chlorogenic acid ( mono ‐CQA and di ‐CQA), were identified in AF. Conclusions: An ultra‐high‐performance liquid chromatography coupled to quadrupole‐time‐of‐flight tandem mass spectrometry with MS E (UPLC–QTOF‐MS E ) analysis with four‐step filtering strategy was established and successfully applied to identify the chemical constituents of AF which can provide chemical support for further research and play an important role in the quality control of AF.